Kegiatan Edukasi Dan Skrining Asam Urat Dalam Pencegahan Terjadinya Gagal Ginjal Kronis Di Usia Dewasa - Sari, Triyana; Santoso, Alexander Halim; Destra, Edwin; Alifia, Tosya Putri; Permatasari, Nabila Jingga (CV. Akira Java Bulu, 2025)
Hyperuricemia is a condition characterized by elevated uric acid levels in the blood, which can increase the risk of chronic kidney failure due to the deposition of uric acid crystals in renal tissue. Education and screening for uric acid levels are crucial for the early detection and prevention of hyperuricemia, particularly in the adult population. This community service program utilized the Plan–Do–Check–Act (PDCA) approach, encompassing counseling on risk factors of hyperuricemia, uric acid level screening with Point Of Care Testing (POCT), and education on strategies to prevent chronic kidney disease. The activity involved 40 participants of productive age, with an average age of 43.97 years. The mean uric acid level was recorded at 5.74 mg/dL. Educational interventions successfully increased participants’ awareness of the importance of maintaining uric acid levels within normal limits. Routine screening enables early identification of at-risk individuals and facilitates timely implementation of preventive measures. This program highlights the importance of public education and early detection in reducing the risk of chronic kidney disease and underscores the role of preventive health efforts in improving overall quality of life. Keywords: Education, Chronic Kidney Failure, Hyperuricemia, Prevention, Screening